Stedman's medical terms and phrases : a complete guide to medical language. - 4 0 16; 5 (Baltimore, Maryland : Lippincott Williams & Wilkins, 2005)
A reference that includes over 240,000 medical terms and phrases from every medical specialty. Content is keyword cross-indexed so that users can find phrases by first or last word.
Includes bibliographical references (page xiii).
Adult;Adult.
Keywords: 2 -- 0; 6; English.;English. -- Medicine;Medicine;Medicine;Medicine -- Terminology.;Terminology.;Phrases;Terminology; 20; 2